O-GlcNAc Transferase Is Essential for Sensory Neuron Survival and Maintenance - Su, Cathy (J Neurosci, 2017)
O-GlcNAc transferase (OGT) regulates a wide range of cellular processes through the addition of the O-GlcNAc sugar moiety to thousands of protein substrates. Because nutrient availability affects the activity of OGT, its role has been broadly studied in metabolic tissues. OGT is enriched in the nervous system, but little is known about its importance in basic neuronal processes in vivo. Here, we show that OGT is essential for sensory neuron survival and maintenance in mice. Sensory neuron-specific knock-out of OGT results in behavioral hyposensitivity to thermal and mechanical stimuli accompanied by decreased epidermal innervation and cell-body loss in the dorsal root ganglia. These effects are observed early in postnatal development and progress as animals age. Cultured sensory neurons lacking OGT also exhibit decreased axonal outgrowth. The effects on neuronal health in vivo are not solely due to disruption of developmental processes, because inducing OGT knock-out in the sensory neurons of adult mice results in a similar decrease in nerve fiber endings and cell bodies. Significant nerve-ending loss occurs before a decrease in cell bodies; this phenotype is indicative of axonal dieback that progresses to neuronal death. Our findings demonstrate that OGT is important in regulating axonal maintenance in the periphery and the overall health and survival of sensory neurons. SIGNIFICANCE STATEMENT We show the importance of O-GlcNAc transferase (OGT) for sensory neuron health and survival in vivo. This study is the first to find that loss of OGT results in neuronal cell death. Moreover, it suggests that aberrant O-GlcNAc signaling can contribute to the development of neuropathy. The sensory neurons lie outside of the blood–brain barrier and therefore, compared to central neurons, may have a greater need for mechanisms of metabolic sensing and compensation. Peripheral sensory neurons in particular are subject to degeneration in diabetes. Our findings provide a foundation for understanding the role of OGT under normal physiological conditions in the peripheral nervous system. This knowledge will be important for gaining greater insight into such disease states as diabetic neuropathy.